2018
DOI: 10.1038/s41598-018-24324-z
|View full text |Cite
|
Sign up to set email alerts
|

MEMS based highly sensitive dual FET gas sensor using graphene decorated Pd-Ag alloy nanoparticles for H2 detection

Abstract: A low power, dual-gate field-effect transistor (FET) hydrogen gas sensor with graphene decorated Pd-Ag for hydrogen sensing applications was developed. The FET hydrogen sensor was integrated with a graphene-Pd-Ag-gate FET (GPA-FET) as hydrogen sensor coupled with Pt-gate FET as a reference sensor on a single sensor platform. The sensing gate electrode was modified with graphene by an e-spray technique followed by Pd-Ag DC/MF sputtering. Morphological and structural properties were studied by FESEM and Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 45 publications
1
55
0
1
Order By: Relevance
“…In addition, the complex alloy formation may increase the response of hydrogenation permeation by increasing the active surface coverage. Furthermore, it was found that Ag alloying with Pd can be advantageous for the embrittlement and mechanical issue of Pd lattice which might be more improved with the Pt/Pd@Ag nanoislands case [76,77]. A higher surface to volume ratio-based Ag nanoislands enhances the bimetal capping configuration that makes a percolation pathway that is suitable for higher carrier mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the complex alloy formation may increase the response of hydrogenation permeation by increasing the active surface coverage. Furthermore, it was found that Ag alloying with Pd can be advantageous for the embrittlement and mechanical issue of Pd lattice which might be more improved with the Pt/Pd@Ag nanoislands case [76,77]. A higher surface to volume ratio-based Ag nanoislands enhances the bimetal capping configuration that makes a percolation pathway that is suitable for higher carrier mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the micro-heaters embedded in the MEMS-based gas sensors reported by the other groups [11,12,33], the micro-heater used in this work can achieve much higher temperature with the same power consumption as displayed…”
Section: Comparison In Power Consumption Of Microheatersmentioning
confidence: 99%
“…In addition, a large size of heater is required to raise the operating temperature due to its large sensing area, resulting in high power consumption [11,12,33]. [13].…”
Section: Various Types Of Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, metal gate materials, such as palladium and platinum, are only sensitive to hydrogen. Recently, many works have been done on the gate design to improve the performance of the FET sensors by applying nanomaterials, such as carbon nanotubes [ 16 ] and graphene [ 17 ], or by a thin charge inversion layer [ 18 ]. MOX gas sensors measure the conductance change of the metal oxide layer and play a dominant role in both research studies and commercial products because they have the most balanced overall performance and low fabrication cost.…”
Section: Introductionmentioning
confidence: 99%